Ethnobotanical knowledge and conservation of Bombax costatum Pellegr. and Vuillet: an overexploited savanna tree species - Zerbo, Issouf; SALAKO, Kolawolé Valère; Hounkpevi, Achille; Zozoda, Djirensolo; GLÈLÈ KAKAÏ, Romain; THIOMBIANO, Adjima (My University, 2022)
In regions dominated by savannahs, multipurpose tree species are key resources considering the diversity of services they offer. Such species are proned to overexploitation and improper management that may threaten their survival. Understanding local perception on their uses and conservation is essential to engage local communities in their sustainable management. This study presents the case-study of Bombax costatum in the semi-arid region of Burkina Faso. Specifically, the study (i) assesses the diversity of uses of B. costatum; (ii) analyse the effect of socio-demographic characteristics of local population on its uses and examine their perceptions of the threats and conservation solutions for B. costatum. Individual semi-structured interviews were conducted with 309 local people in Burkina Faso. Data were gathered on informants’ sociodemographic characteristics, use categories, plant parts used and perceived conservation concerns. Descriptive statistics, Principal Components Analysis, and Non-parametric models were used for data analysis. Ten plant parts of the species are used for nine use categories. Food (44.52%), medicine (19.99%), fodder (15.16%) and handicrafts (14 .33%) were the most cited use categories. The most used plant parts were leaves (30.83%), flowers (25.03%), trunk (16.62%) and bark (14.70%). Leaves, flowers, twig bark and petioles were used as food and fodder. Trunk bark, root and resin were used in medicine. Trunk and whole plant were used in handicraft, construction, culture, honey production and spirituality. The harvest of B. costatum plant parts for food uses varied cyclically. Ethnicity, age, education level and main activity were the most influencing sociodemographic factors for the species uses. Furthermore, local population shared the same opinion (Sorensen index > 0.50) on the areas of abundance, threat factors and conservation solutions. They reported the species as abundant in agrosystems (47.08 %), forests (29.57 %) and rocky and granite hills (22.00 %). The main threat factors were tree cutting (32.5 %) and pruning (15.51 %). For its conservation, local people recommended mostly domestication (39.29 %) and strengthening of conservation measures (14.84 ± 2.99 %). This study reveals the importance of B. costatum while also highlighting essential aspects to consider to successfully engage farmers for its sustainable management.
Keywords: Local knowlege; Agrofoforestry; Threaten factor; Conservation solutions